Cas-OFFinder: a fast and versatile algorithm that searches for potential off-target sites of Cas9 RNA-guided endonucleases - Bae, Sangsu; Park, Jeongbin; Kim, Jin-Soo (Bioinformatics, 2014)
The Type II clustered regularly interspaced short palindromic repeats (CRISPR)/Cas system is an adaptive immune response in prokaryotes, protecting host cells against invading phages or plasmids by cleaving these foreign DNA species in a targeted manner. CRISPR/Cas-derived RNA-guided engineered nucleases (RGENs) enable genome editing in cultured cells, animals and plants, but are limited by off-target mutations. Here, we present a novel algorithm termed Cas-OFFinder that searches for potential off-target sites in a given genome or user-defined sequences. Unlike other algorithms currently available for identification of RGEN off-target sites, Cas-OFFinder is not limited by the number of mismatches and allows variations in protospacer-adjacent motif sequences recognized by Cas9, the essential protein component in RGENs. Cas-OFFinder is available as a command-line program or accessible via our website. Availability and implementation: Cas-OFFinder free access at http://www.rgenome.net/cas-offinder. Contact: baesau@snu.ac.kr or jskim01@snu.ac.kr